Apresentação PBCIB n.1 v.2, 2007 - Freire, Isa Maria; Freire, Gustavo Henrique de Araújo; Araújo, Vânia Maria Rodrigues Hermes de (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2007)
Apresentação do fascículo 1 do volume 2 da PBCIB